Desenvolvimento de sistemas de controle tolerante a falhas por alocação de controle - Sousa, Nádia Guimarães (2014)
The industrial process control has suffered significant changes due to pressures associated with increased competition, rapid changes in economic conditions and stricter environmental laws, thereby promoting its modernization in chemical plants. Therefore, more sophisticated control strategies, which are able to tolerate failures and ensure an effcient response, are easily justifiable to maintain the plant operation close to the economic optimum and within the safety limit. In this sense, it is proposed in this work the study and implementation of allocation control methodologies applied to fault tolerant control in chemical processes. The main feature of control allocation method is the redundancy of actuators, which can improve performance and reliability of system control. In this approach, control law establishes the total control effort required and the distribution of control signals is determined separately by a control module allocation, especially in the presence of faults on actuators. The control law, called virtual control may be any type of control strategy (MPC, PI, PID etc). Thus, this thesis introduces allocation control methods based on factoring and reference model for continuous and discrete algorithms using the l1 and l2 norms. The allocation control problem based on factorization is illustrated by the study of two types of controllers: (i) MPCA in which virtual control consists of an MPC (Model Predictive Control) and (ii) CA-PI wherein virtual control consists of a PI (Proportional-Integral). For control allocation technique based on the reference model it is evaluated a reference model of PI type applied to minimal and non minimum phase systems. Benets of these techniques are investigated in the management of constraints for manipulated variables when implemented on Chemical Engineering linear and nonlinear systems. The proposed strategies were evaluated using open source software Scilab®, in which scenarios with faults in actuators were tested. For all studies it was observed the ability of the proposed strategies on relocating the control signals among the available actuators, minimizing the fault effect. Based on results it is clear that control allocation provides exibility to address control systems with actuator failures and this technique allows the distribution of control efforts for available manipulated variables.